Plaza de Desierto, Baracaldo - Arroyo, Eduardo (2002)
Plaza en el corazón de un barrio residencial que recupera un área industrial degradada
Keywords: ESPAÑA; VIZCAYA; BARACALDO; PLAZAS; ESPACIO PUBLICO; REHABILITACION; RENOVACION URBANA